STRATEGI KEWIRAUSAHAAN DAN KEPEMIMPINAN DALAM PENGEMBANGAN USAHA KECIL - Tata Khairina Daulay; Chelsea Oktavia Purba; Yusniar; Zulaika Syah putri; Nela Permata Sari (STKIP Subang, 2026)
This study aims to analyze entrepreneurship and leadership strategies in the development of small businesses. The research method used is qualitative research with a literature study approach through collecting data from scientific journals, books, and previous studies relevant to the research topic. The results show that entrepreneurial strategies play an important role in increasing the competitiveness of small businesses through innovation, creativity, the ability to identify business opportunities, and the use of digital technology. In addition, entrepreneurial leadership also influences the success of small businesses because it helps business management, decision-making, and improving work motivation. The use of digital technology is one of the important factors in expanding marketing and increasing the effectiveness of small businesses in the modern era. Based on the research results, it can be concluded that entrepreneurial and leadership strategies have a close relationship in supporting sustainable small business development. Therefore, small business actors are expected to improve innovation skills, leadership abilities, and the use of digital technology so that their businesses can develop and have high competitiveness.